PERAN KEMENTERIAN AGAMA KABUPATEN GOWA DALAM MENGANTISIPASI PERMASALAH BIRO PENYELENGGARAAN IBADAH UMRAH PERIODE 2021 (Fakultas Dakwah dan Komunikasi, 2021)
This study discusses the role played by the Ministry of Religion of Gowa Regency in an effort to anticipate the problems that often occur in the Umrah organizing bureau. This study aims to determine the implementation of the Umrah bureau in Gowa Regency for the period of 2021 and to determine the function of the Ministry of Religion in organizing Umrah in Gowa Regency.This study uses a qualitative research type with a scientific approach, namely management, especially in the supervision of the Umrah travel agency. Methods of data collection through in-depth interviews, literature study, observation, documentation and online search. The analysis technique is data reduction, data presentation, and conclusion drawing.The results of this study indicate that 1) The implementation of the Gowa Regency Umrah travel agency for the 2021 period has not run optimally, because there is still a Covid-19 outbreak where pilgrims must meet the conditions for departure during the Covid-19 pandemic and apply health protocols. In addition, the additional costs for pilgrims who will depart, also have an impact on the number of prospective pilgrims who fail to depart in 2021. Then the quota for the State of Indonesia is still limited, and the provisions of the Saudi Arabian Government are uncertain. 2) The function of the Ministry of Religion in organizing Umrah in Gowa Regency is that there are still functions of the Regency / City Ministry of Religion that have not been carried out systematically, so efforts are needed to evaluate and maximize their functions or authorities regarding the function of service and coaching (both socialization, direct field inspections) , and coordination of travel bureaus for Umrah/travel), as well as those related to the programmatic and periodic supervisory function that must be carried out by the Regency/Municipal Ministry of Religion. In addition, because there are still victims of fraud that occur because the public is still easy to be deceived if they have been given the lure at low prices. The implementation of this research is that the role of the Gowa Regency Ministry of Religion, especially in the Hajj and Umrah Organizing Section of the Umrah Worship Travel Bureau is administratively focused on the laws and regulations, the regulations of the Minister of Religion of the Republic of Indonesia and the Decree of the Director General for the Implementation of the Umrah Worship then follow the standard operational rules that have been set. issued within the scope of the Gowa Regency Ministry of Religion Office in anticipating problems with the Umrah Organizing bureau. Keywords: Umrah Service Organizing, Umrah Organizing Bureau, Ministry of Religion Gowa